Harry Augustus Garfield papers - Garfield, Harry Augustus, 1863-1942.; Comer, Lucretia Garfield, 1894-1968.; Garfield, Harry Augustus, 1863-1942.; Williams College. Institute of Politics
Correspondence, diaries, speeches, writings, articles, legal case files, subject files, financial records, biographical material, family papers, scrapbooks, clippings, photographs, and other papers relating to Garfield's career as a lawyer, professor, and university administrator; his interest in politics and international affairs; and his associations as the son of President James A. Garfield. Documents his years as professor of politics at Princeton University; as president of Williams College including his establishment and administration of the college's Institute of Politics; his service as head of the U.S. Fuel Administration during World War I; and his work as a lawyer in Cleveland, Ohio. Subjects include consular reform, international relations, municipal reform in Cleveland, Ohio, world peace, and family matters. Includes the manuscript of Garfield's autobiography, Lost Visions (1944) and papers collected by Lucretia Garfield Comer for use in Harry Garfield's First Forty Years: Man of Action in a Troubled World (1965). Also includes speeches, articles, and other records of the Institute of Politics. Correspondents include Newton D. Baker, William Jennings Bryan, Calvin Coolidge, Lucretia Rudolph Garfield, John Hay, Herbert Hoover, Charles Evans Hughes, William McKinley, Franklin D. Roosevelt, Theodore Roosevelt, William H. Taft, and Woodrow Wilson.
Lawyer, educator, public official, and son of President James A. Garfield.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
List of Garfield's speeches and writings available in the Library of Congress Manuscript Division.
Keywords: Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Coolidge, Calvin, -- 1872-1933 -- Correspondence; Garfield, James A. -- 1831-1881 -- Family; Garfield, Lucretia Rudolph, -- 1832-1918 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; McKinley, William, -- 1843-1901 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Garfield family; United States. -- Fuel Administration; Princeton University; Williams College; Williams College. -- Institute of Politics; Diplomatic and consular service, American; International relations; Municipal government -- Ohio -- Cleveland; Peace; Political science -- Study and teaching -- United States; Practice of law -- Ohio -- Cleveland; World War, 1914-1918 -- Fuel supplies; Cleveland (Ohio) -- Politics and government; Educators; Lawyers; Public officials